2008
DOI: 10.1590/s0100-204x2008000300005
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento de afilhos e componentes do rendimento em genótipos de trigo sob diferentes densidades de semeadura

Abstract: Resumo -O objetivo deste trabalho foi determinar o padrão de desenvolvimento de afilhos em genótipos de trigo contrastantes para esse caráter, em diferentes densidades de semeadura, bem como seus efeitos sobre os componentes do rendimento de grãos. O experimento foi conduzido no Município de Capão do Leão, RS, em 2006. Dez cultivares de trigo, selecionadas com base na capacidade de afilhamento, foram utilizadas em delineamento de parcelas divididas, com a parcela composta pelo fator cultivar, e as subparcelas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
21

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 13 publications
1
55
0
21
Order By: Relevance
“…De maneira semelhante, Valério et al (2008) observaram que a emissão de espigas apresentou resposta diferenciada às densidades de semeadura, para cada cultivar. Entretanto, no presente Letras minúsculas comparam entre linhas (cultivares) e letras maiúsculas comparam entre colunas (locais).…”
Section: Resultsunclassified
See 2 more Smart Citations
“…De maneira semelhante, Valério et al (2008) observaram que a emissão de espigas apresentou resposta diferenciada às densidades de semeadura, para cada cultivar. Entretanto, no presente Letras minúsculas comparam entre linhas (cultivares) e letras maiúsculas comparam entre colunas (locais).…”
Section: Resultsunclassified
“…Médias seguidas de mesma letra não diferem entre si, pelo Teste Tukey, a 5%. mudanças na massa de mil sementes são observadas porque a planta de trigo é bastante plástica, em relação ao efeito de densidades de semeadura (Valério et al 2008). Contudo, a amplitude das alterações na massa de mil sementes não é elevada, porque esta é uma característica controlada geneticamente (Guarienti 2005).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Plants density per area is a decisive factor in the development of a species if seeking maximum production (Valério et al, 2008). Productivity variation in relation to plant population is associated with the genotype potential to produce fertile tillers, since the sowing density directly influences the number of spikes and/or panicles produced by area (Ozturk et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Productivity variation in relation to plant population is associated with the genotype potential to produce fertile tillers, since the sowing density directly influences the number of spikes and/or panicles produced by area (Ozturk et al, 2006). Cultivar selection alone can indicate differences to better fit the population density, due to directly influencing tillering capacity, which is a directly connected component to grain productivity (Valério et al, 2008). Valério et al (2009) reported that senescence and tillers survival is related to the cultivar tillering potential, since reduced expression genotypes are more dependent on sowing density for maximum grain yield.…”
Section: Introductionmentioning
confidence: 99%